(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Arab-Chinese relations are represented as relations of great importance, they are relations dating back to a long time, and political relations are the main axis of the foreign relations that exist between countries. A pioneer in this field, despite her novelty at the beginning, she was able to establish various forms of external relations, and political relations were the most prominent of these images The research dealt with a reading in the history of Arab-Chinese relations from the political point of view from the beginning of Islam until the end of the Umayyad era. It is an ancient relationship and a precedent for the emergence of Islam. Policies of China towards the Muslims living in it, as well as a look at the political situation inside China of the Tang Dynasty and its reflection on Muslims there. The research consisted of seven axes that included: the naming and geography of China in addition to the political development of China during the Tang Empire and the accompanying emergence and development of Arab-Chinese relations in the adult era, and the efforts of Arab Muslims to open China during this era. The research also touched on the path taken by Islam to reach To the land of China, the Arab-Islamic conquests during the Umayyad period and conquered Kashgar. Finally, the research dealt with the Arab-Chinese embassies exchanged during the research period. The research concluded in the conclusion to highlight the most important results of the research in this field.